+0  
 
0
103
1
avatar

y=f(-x)

Guest Mar 5, 2017
Sort: 

1+0 Answers

 #1
avatar+1814 
+10

1. Multiplying a positive and a negative equals a negative

\(y=f\times (-X)\)

 

2. The final solution for y is

\(y=-fX\)

 

3. Answer

\(y=-fX,f\in\mathbb{R},X\in\mathbb{R}\)

edited by EighthMersennePrime  Mar 5, 2017

5 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details